Analisis Laporan Keuangan dengan Menggunakan Metode Trend sebagai Dasar Menilai Kondisi Perusahaan - Nur Ilmi Octaviani; Erry Sunarya; Kokom Komariah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Financial statements are actually still a problem in a company that really needs to be taken seriously because the good and bad financial statements describe the company's financial condition. The purpose of this research is to find out how the company's financial condition and comparison of predictions of financial statements at PT. Three Pillars of Prosperous Food Tbk. The research method used in this study is a descriptive method with a quantitative approach, in which the authors collect data in the form of balance sheet financial position reports. Data collection techniques used were documentation and literature study. The results of this study indicate that there is a fluctuating development in the balance sheet and income statement, even in the balance sheet from year to year it also fluctuates, the income statement has increased from 2014 to 2016 and always decreases in 2017 Conclusion, by using trend analysis it can be predicted that the value of the postal year will come to experience a fluctuating development which is also the same as in previous years. Keywords: Financial Statements, Trend Methods, Company Conditions